Oxidative Modification in the Salivary Glands of High Fat-Diet Induced Insulin Resistant Rats - Kołodziej, Urszula; Maciejczyk, Mateusz; Miąsko, Agnieszka; Matczuk, Jan; Knaś, Małgorzata; Żukowski, Piotr; Żendzian-Piotrowska, Małgorzata; Borys, Jan; Zalewska, Anna (Frontiers in Physiology, 2017)
Still little is known about the role of oxidative stress (OS) in the pathogenesis of the salivary gland dysfunction in the course of insulin resistance (IR). To induce IR rats was fed with a high fat diet (HFD) during 8 weeks. Stimulated and non-stimulated salivary flow rate, total protein, as well as oxidative damage markers: 4-HNE protein adduct, 8-isoprostanes (8-isoP), 8-hydroxy-D-guanosine (8-OHdG), advanced oxidation protein product (AOPP) and protein carbonyls (PC) were determined in the plasma and submandibular and parotid glands of IR and control rats. We have shown a significant decrease (45%) of the stimulated salivary flow rate, and in the total protein concentration in the parotid (35%) and submandibular (10%) glands of HFD IR as compared to the control rats. The level of 4-HNE protein adduct (15%) and 8-isoP (20%) in the submandibular glands of IR rats as well as total level of 4-HNE protein adduct (39%), 8-isoP (27%), AOPP (25%), PC (32%), and 8-OHdG (18%) in the parotid glands of IR rats were significantly higher as compared to the control group. We showed no correlation between the assessed OS parameters in the plasma and salivary glands. However, the redox balance in both glands shifted toward the oxidative status, parotid glands of IR rats are exposed to greater intensity OS. Stimulated secretory ability and mechanisms involved in the synthesis/secretion of proteins in the salivary glands are depressed in the course of IR. Oxidative damage in the salivary glands arises independently from the general oxidative stress in the course of insulin resistance induced by a high fat diet.